Tooth Root Size, Chewing Muscle Leverage, and the Biology of Homunculus patagonicus (Primates) from the late early Miocene of Patagonia (Ameghiniana, 2010)
Inferences about the diet of Miocene platyrrhine monkeys have relied upon the morphology of the molar teeth, specifically the crests on the molars. Using a library of Micro-CT images of a broad comparative sample of living platyrrhines (callitrichines, cebines, pitheciids and atelids), late early Miocene Homunculus, and the early Miocene Tremacebus and Dolichocebus, we extend these inferences by examining the surface areas of the tooth roots, anchor points for the periodontal ligaments. From muscle scars on the skull, we estimate the mechanical leverage of the chewing muscles at bite points from the canine to the last molar. Extant platyrrhines that gouge bark to obtain exudates do not have especially large canine roots or anterior premolar roots compared with their less specialized close relatives. Extant platyrrhines that have more folivorous diets have much larger molar roots than do similar-sized more frugivorous species. Homunculus patagonicus has large postcanine roots relative to body size and poor masticatory leverage compared to the extant platyrrhines in our sample. The large postcanine roots, heavy tooth wear, and moderately-long shearing crests suggests a diet of abrasive, resistant foods. However, relatively poor jaw adductor leverage would have put the masticatory apparatus of Homunculus at a mechanical disadvantage for producing high bite forces compared to the condition in extant platyrrhines. Tremacebus and Dolichocebus, like Homunculus, have larger tooth root surfaces than comparable-sized living platyrrhines. They also resemble Homunculus in being more prognathic and having posteriorly-located temporalis origins - all features of a relatively poor leverage system.Resumen. TAMAÑO DE LAS RAÍCES DENTARIAS, BRAZOS DE PALANCA DE LA MUSCULATURA MASTICATORIA Y BIOLOGÍA DE HOMUNCULUS PATAGONICUS (PRIMATES) DEL MIOCENO TEMPRANO DE PATAGONIA. Las inferencias sobre dieta de monos platirrinos miocenos se han basado en la morfología de los molares, específicamente las crestas. Aquí se estudia la superficie de las raíces de los dientes, área de anclaje del ligamento periodontal. Se utilizó una base de datos de imágenes Micro-CT de platirrinos actuales (calitriquinos, cebinos, pitécidos y atélidos), Tremacebus y Dolichocebus (Mioceno temprano) y Homunculus patagonicus (Mioceno temprano tardío). Basándose en las cicatrices musculares preservadas en los cráneos, se estimó el brazo de palanca de los músculos masticatorios en puntos de mordida desde el canino hasta el último molar. En los platirrinos actuales que se alimentan de exudados, las raíces de los caninos o premolares anteriores no son especialmente grandes; en los folívoros, las raíces de los molares son mucho más grandes que en los frugívoros de tamaño similar. Las raíces de los postcaninos de H. patagonicus son más grandes en relación a su tamaño corporal que en cualquier otro platirrino viviente analizado; las raíces postcaninas grandes, el excesivo desgaste de los dientes y las crestas cortantes moderadamente largas sugieren un consumo de alimentos abrasivos y resistentes. Sin embargo, la palanca aductora relativamente pobre de la mandíbula indica una desventaja mecánica para producir fuerzas de mordida elevadas en comparación con platirrinos actuales. Tremacebus y Dolichocebus también poseen superficies de las raíces más grandes que los platirrinos vivientes de tamaño equivalente y se asemejan a Homunculus por ser más prognatos y por el origen del músculo temporal ubicado posteriormente, rasgos que indican un sistema de palancas relativamente pobre.